MANAGEMENT OF DIABETIC PATIENTS UNDERGOING ORAL SURGERY PROCEDURES: A NARRATIVE REVIEW - Miśkiewicz, Emilia; Borek, Natalia; Gałązka, Julia; Stopa, Ewa; Krupa, Hanna; Wieczorek, Zofia; Kędrak, Magdalena; Stanisławski, Dominik; Jabłońska-Trzosek, Wiktoria; Pochwalski, Jakub (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Diabetes mellitus is a systemic metabolic disorder that requires careful perioperative management in oral and maxillofacial surgery. Aim: To synthesize the current evidence on the perioperative management of diabetic patients undergoing oral surgery, with emphasis on preoperative assessment, glycemic control, medication adjustment, intraoperative precautions, and postoperative care. Material and methods: This narrative review searched PubMed/MEDLINE and Google Scholar using terms related to diabetes mellitus, oral surgery, tooth extraction, perioperative management, glycemic control, HbA1c, antibiotic prophylaxis, wound healing, and postoperative complications. Twenty-three publications met the inclusion criteria. Results: The literature shows that diabetes is a clinically relevant perioperative risk factor in oral surgery. Evidence on extraction healing is mixed: some studies found no significant effect of glycemic control on post-extraction healing, while others reported more unhealed sockets in patients with poorer glycemic control. The available evidence does not consistently support routine antibiotic prophylaxis for simple extractions. Conclusions: Diabetes increases the perioperative risk in oral surgery, however, it is not a contraindication to treatment when patients are properly assessed and prepared. Individualized preoperative evaluation, glycemic control, careful surgical technique, and close postoperative follow-up are essential for safe management of these patients.